Α-Amylase immobilization on amidoximated acrylic microfibres activated by cyanuric chloride. Issue 11 (28th November 2018) - Almulaiky, Yaaser Q.; Aqlan, Faisal M.; Aldhahri, Musab; Baeshen, Mohammed; Khan, Tariq Jamal; Khan, Khalid A.; Afifi, Mohamed; AL-Farga, Ammar; Warsi, Mohiuddin Khan; Alkhaled, Mohammed; Alayafi, Aisha A. M.
Abstract : Enzyme immobilization is one of the most important techniques for industrial applications. It makes the immobilized enzyme more stable and advantageous than the free form in different aspects. α-Amylase was immobilized on 4% cyanuric chloride-activated amidoximated acrylic fabric at pH 7.0 with (79%) maximum efficiency. A field emission scanning electron microscope and Fourier transform infrared were used to confirm the immobilization process. Even after being recycled 10 times, the immobilized enzyme lost just 28% of its initial activity. Owing to immobilization, the pH of the soluble α-amylase was shifted from 6.0 to 6.5. The immobilized α-amylases showed thermal stability at 60°C, and became more resistant to heavy metal ions. The k m values of the immobilized and soluble α-amylases were 9.6 and 3.8 mg starch ml −1, respectively. In conclusion, this method shows that the immobilized α-amylase proved to be more efficient than its soluble form, and hence could be used during saccharification of starch.